Determining physical-chemical patterns during the formation of brazed joints between tungsten and carbon-carbon composite material - Huba, Roman; Kamkina, Liudmyla; Bushtruk, Serhii; Troian, Andrii; Asmolovskyi, Serhii; Oslavskyi, Serhii (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates experimentally produced brazed joints between carbon-carbon composite material (CCCM) and tungsten in a vacuum. The task addressed is to obtain high-temperature brazed joints capable of operating at temperatures of 1400–1600°C in a vacuum under conditions of high thermal cycling loads. Existing methods for joining CCCM with tungsten testify for a virtual lack of experience in brazing such materials, especially for structures of thermal emission equipment. In this work, a method was used to produce a metallized layer zone with partial melting using a mixture of Ti-Nb-Zr powders on the inner surface of an CCCM sample. Subsequently, the CCCM and tungsten samples were brazed with a Ti-Nb filler metal at a temperature of 1840°C in a vacuum. The results of microstructural analysis revealed that the brazed joint exhibits a zonal structure. Zone I – a reaction carbide layer (width 10–12 μm), zone II – diffusion layer (width up to 70 μm), zone III – reaction layer adjacent to tungsten (width up to 30 μm). The results of phase formation modeling conducted at a temperature of 1840°C indicate the predominant formation of TiC, NbC, Nb6C5, and Nb2C. Additionally, the distribution of C, Ti, Nb, and W in the brazed joint was determined. The results of the microhardness study confirmed the accuracy of the simulation and showed that microhardness values decrease from Zone I (2300 HV) to Zone III (500–600 HV). The proposed solutions demonstrate that the metallized layer helps retain solder in the joint gap; reduces thermomechanical stresses; and promotes the formation of a gradual hardness gradient. Together, these characteristics improve the ductile properties of the brazed joint. The results of this study could be applied in the field of instrument engineering, specifically in the manufacture of cathode components whose emitters are made from ultrafine powders of rare-earth borides or their alloys